Comparative microRNA profiling of Trypanosoma cruzi infected human cells - Rego, Natalia; Libisch, María Gabriela; Rovira, Carlos; Tosar, Juan Pablo; Robello, Carlos (Frontiers in Cellular and Infection Microbiology, 2023)
Trypanosoma cruzi, the causative agent of Chagas disease, can infect almost any nucleated cell in the mammalian host. Although previous studies have described the transcriptomic changes that occur in host cells during parasite infection, the understanding of the role of post-transcriptional regulation in this process is limited. MicroRNAs, a class of short non-coding RNAs, are key players in regulating gene expression at the post-transcriptional level, and their involvement in the host-T. cruzi interplay is a growing area of research. However, to our knowledge, there are no comparative studies on the microRNA changes that occur in different cell types in response to T. cruzi infection. Here we show that, although microRNAs are highly cell type-specific, a signature of three microRNAs -miR-1246, miR-146a and miR-708, emerges as consistently responsive to T. cruzi infection across representative human cell types. T. cruzi lacks canonical microRNA-induced silencing mechanisms and we confirm that it does not produce any small RNA that mimics known host microRNAs. We performed RNA sequencing of small RNAs of epithelial cells, cardiomyocytes and macrophages infected with T. cruzi for 24 hours, followed by careful bioinformatics analysis. We found that macrophages show a broad response to parasite infection, while microRNA changes in epithelial and cardiomyocytes are modest. Complementary data indicated that cardiomyocyte response may be greater at early time points of infection. Our results highlight the importance of considering microRNA changes at the cellular level and contribute to previous studies that addressed them at higher organizational levels (e.g. heart samples). miR-146a has been previously implicated in T. cruzi infection, as it happens to be in many other immunological responses, but miR-1246 and miR-708 are first shown here. As they are expressed in many cell types, we anticipate our work as a starting point for more studies investigating their role in post-transcriptional regulation of T. cruzi infected cells as well as their potential use as Chagas disease biomarkers.